2020
DOI: 10.21203/rs.3.rs-29205/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of High-Risk Fertility Behavior on Under-five Mortality in Asia and Africa: Evidence from Demographic and Health Surveys

Abstract: Background High-risk fertility behaviors (HRFBs) are common in African and South Asian countries and can potentially affect child survival. This study examines the high-risk fertility behaviors concerning child mortality across the countries. Method Data from a series of Demographic and Health Surveys from the year 1987 to 2016 from 24 South Asian and African countries (N=1,224,832) were included in this study. Four HRFB parameters - women’s age <18 or >=34 years at childbirth, birth spacing <24 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
6
4
0
Order By: Relevance
“…Furthermore, other predictors of infant death found in our study are being a male child, small birth size, living in the North west and North East regions, rural place of resident, failure to receive tetanus injection and presence of unskilled birth delivery assistant. This is consistent with research ndings from similar studies [26,29,30]. Our study also found that non-use of contraceptive commodities among the mothers increased the risk of infant mortality as compared with mothers that used contraceptives.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, other predictors of infant death found in our study are being a male child, small birth size, living in the North west and North East regions, rural place of resident, failure to receive tetanus injection and presence of unskilled birth delivery assistant. This is consistent with research ndings from similar studies [26,29,30]. Our study also found that non-use of contraceptive commodities among the mothers increased the risk of infant mortality as compared with mothers that used contraceptives.…”
Section: Discussionsupporting
confidence: 93%
“…Children born to women who engaged in double high-risk fertility behaviors were more likely to die as compared to children born to women who were no high-risk fertility behavior. This finding was supported by previous studies [16,24]. Moreover, the odds of under-five mortality among children of women who were engaged in three high-risk fertility behaviors was higher compared to children of women who have not engaged in any high-risk fertility behavior [16].…”
Section: Discussionsupporting
confidence: 87%
“…However, the current study shows that single high-risk fertility behavior was not associated with under-five mortality. This finding was agreed with the previous study; too early childbearing (<18 years) [16], too late childbearing age [24], and too many births (>3) [16,24] were not associated with under-five mortality. However, short birth interval space (<24 months) [16,24] and too late childbearing age (>40) [16] were associated with under-five mortality.…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…Maternal HRFB is a bio-demographic risk factor that impedes the achievement of lower maternal and child morbidity and mortality [4][5][6][7][8]. Some demographic variables, such as women's age, parity, and birth spacing are the crucial parameters of measuring HRBF including too-early (<18 years) or too-late (>34 years) childbearing, short birth intervals (<24 months) and a higher number of live births (4 or higher) [4,5,[8][9][10]. Although the total fertility rate (TFR) of Bangladesh declined from 3.7 in 1995 to 2.04 in 2020 [1].…”
Section: Introductionmentioning
confidence: 99%